Memaknai Kearifan Lokal Tidur di Atas Pasir sebagai Representasi Ekologi Budaya Masyarakat Pesisir Pulau Madura - Moh. Wahyu Kurniawan Zain; Corrie Teresia Purba roni; Ardyanto Tanjung; I Komang Astina (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
The challenges of modernization that threaten local wisdom necessitate an in-depth study of the Madurese tradition of Tedung e Bedhih, which has not been widely analyzed from a cultural ecology perspective. This tradition is a form of local wisdom that has profound meaning in terms of health, spirituality, and ecological sustainability, utilizing sand that contains natural elements such as calcium oxide, zinc, and copper, which are believed to have therapeutic benefits, such as warming the body and relieving joint pain, and relying on natural heat energy from the sun stored in the sand as a substitute for modern technology. This study aims to explore the reasons behind this practice and how this tradition maintains the ecological and spiritual balance of the local community. Using a descriptive qualitative approach, this study analyzes the relationship between the tradition of sleeping on sand and the surrounding environmental conditions and how this practice reflects a lifestyle that is in harmony with nature. The subjects consisted of three key informants from Leggung Timur Village to ensure depth and diversity of data. The results of the study show that this tradition is not only a form of habit, but also has deep ecological value and contributes to the sustainable preservation of sand resources. Although modernization threatens its sustainability, this tradition reflects the community's knowledge system. The subjects consisted of three key informants from Leggung Timur Village to ensure the depth and diversity of the data. The results of the study show that this tradition is not only a custom, but also has profound ecological value and contributes to the sustainable preservation of sand resources. Although modernization threatens its continuity, this tradition reflects the knowledge system of coastal communities, which represents the knowledge and practices of coastal communities that reflect an awareness of living in harmony with nature and utilizing resources wisely.